Bond behaviour of GFRP reinforcement in alkali activated cement concrete. (15th November 2017) - Tekle, Biruk Hailu; Khennane, Amar; Kayali, Obada
Highlights: Experimental and numerical study of bond of GFRP reinforced AAC concrete is performed. GFRP reinforced AAC concrete has a similar bond-slip curve with GFRP reinforced OPC concrete. Bond stress has a non-uniform distribution along the embedment length. Bond stress distribution is dependent on the embedment length of bar. Abstract: Bond plays a key role in the performance of reinforced concrete structures. Glass fiber reinforced polymer (GFRP) reinforcing bar and alkali activated cement (AAC) concrete are promising alternative construction materials for steel bars and Ordinary Portland Cement (OPC) concretes respectively. In this study, the bond behaviour between GFRP bars, and AAC and OPC concretes is investigated by using beam-end test specimens. Sand-coated GFRP bars with 12.7 mm and 15.9 mm diameters and embedment lengths of six and nine times the bar diameter were used. The free end and the loaded end bond slip relationships, the failure mode and the average bond stress were used to analyse each of the specimens. Additionally, the distribution of tensile and bond stress along the embedment length was investigated by installing strain gauges along the embedment length. The results of the study indicate that the tensile and bond stress distribution along the embedment length are nonlinear, and the nonlinearity changes with the load. Finite element analysis was also performed to further study the bond stress distribution along the embedment length of the bar. From the finite element analysis, it was found that the bond stress distribution depends on the embedment length of the specimens; approaching uniform distribution as the embedment length decreases.